2011
DOI: 10.1016/j.compedu.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender and gender pairing in the knowledge elaboration processes of students using computer-supported collaborative learning

Abstract: The aim of the study is to investigate the influence of gender and gender pairing on students' learning performances and knowledge elaboration processes in Computer-Supported Collaborative Learning (CSCL). A sample of ninety-six secondary school students, participated in a two-week experiment. Students were randomly paired and asked to solve several moderately structured problems concerning Newtonian mechanics. Students' pretest and posttest performances were analyzed to see whether students' gender and the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
1
35
1
1
Order By: Relevance
“…Additionally, although higher-education computer-science students overwhelmingly tweeted constructive comments that encouraged class discussion, there were also examples of students tweeting unrelated comments [21]. Other potential drawbacks to "Mixed Synchronous" CSCL included the additional time communicating via chat took as compared to face-toface interactions [30] and the finding that mixedgender pairing may negatively affect secondary education female achievement in physics problem solving [10]. For example, female students placed in a mixed gender dyad performed relatively worse on a posttest than females in single gender dyads.…”
Section: Cluster 4: Mixed Synchronousmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, although higher-education computer-science students overwhelmingly tweeted constructive comments that encouraged class discussion, there were also examples of students tweeting unrelated comments [21]. Other potential drawbacks to "Mixed Synchronous" CSCL included the additional time communicating via chat took as compared to face-toface interactions [30] and the finding that mixedgender pairing may negatively affect secondary education female achievement in physics problem solving [10]. For example, female students placed in a mixed gender dyad performed relatively worse on a posttest than females in single gender dyads.…”
Section: Cluster 4: Mixed Synchronousmentioning
confidence: 99%
“…Three of these sampled papers quantitatively examined the effectiveness of particular tools with synchronous dyads in controlled settings [8,20,37]. An additional sampled paper used mixed methods to examined how gender pairings affected student's' knowledge elaboration processes and learning achievement [10]. In all four of these sampled papers, the authors found their CSCL tools to be particularly beneficial to student learning.…”
Section: Cluster 4: Mixed Synchronousmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender has been associated with online discussion message scores. For example, Ding, Bosker, and Harskamp (2011) found that females tend to raise more questions than males in order to open or elicit a discussion. Various studies have shown that GPA to be associated with knowledge gain scores (see Lee & Wu, 2013, for a meta-analyses), and, therefore, we included it as a demographic variable.…”
Section: Control Variablesmentioning
confidence: 99%